A CXCL ortholog from Hippocampus abdominalis: Molecular features and functional delineation as a pro-inflammatory chemokine. Issue 67 (August 2017) - Oh, Minyoung; Bathige, S.D.N.K.; Kim, Yucheol; Lee, Seongdo; Yang, Hyerim; Kim, Myoung-Jin; Lee, Jehee
Abstract: Chemokines are a family of chemotactic cytokines that regulate leukocyte migration. They are classified into four groups namely, CXC, CC, C and CX3 C, based on the formation of a disulfide bridge. Among these, CXC chemokines have been identified as the largest group of chemokines in humans. In this study, we identified and functionally characterized a homolog of CXC chemokine from the big-belly seahorse, Hippocampus abdominalis, and designated it as ShCXCL. The cDNA of ShCXCL composed of a 342-bp open reading frame encoding 113 amino acids (aa). The CXC family-specific small cytokine domain (SCY) was identified from the mature peptide region, which comprised of a conserved CXC motif. As ShCXCL lacks an ELR (Glutamic acid-Leucine-Arginine) motif, it belongs to ELR − subfamily. The recombinant ShCXCL protein strongly induced the nitric oxide (NO) production in macrophage cells (RAW 264.7 cell line) and showed the chemotactic effect on flounder peripheral blood leukocytes. Tissue profiling showed a ubiquitous expression pattern in all examined tissues, with a high abundance in spleen. The up-regulated mRNA expression pattern of ShCXCL was observed in blood and kidney tissues after immune stimulation by live bacteria, such as Streptococcus iniae and Edwardsiella tarda, and mitogens, such as lipopolysaccharides (LPS) and polyinosinic:polycytidylic acid (poly I:C), suggesting its important role in host immune defense against microbial infection. Highlights: A CXC chemokine gene (ShCXCL) with CXC family features was identified. ShCXCL transcripts were constitutively expressed with highest expression in spleen. Modulated transcription of ShCXCL upon challenges revealed its role in host immunity. rShCXCL strongly induced the NO production in RAW 264.7 cells. rShCXCL showed an effective chemotactic activity towards leukocytes.